METHODOLOGICAL-FUNCTIONAL MODEL OF THE PROCESS OF DETERMINING AND DEVELOPING ABILITY IN MOTHER LANGUAGE LESSONS - Raimberdiev Askarjon Asrorovich (The Conference Hub, 2025)
A methodological and functional model of the process of identifying and developing giftedness in native language lessons is presented. In addition, consistent measures are considered in our country to support promising young people, create additional conditions for the realization of their talents, and effectively launch research and innovation activities.
Keywords: talent, giftedness, gifted children, gifted youth, talent, positive talent.